1994
DOI: 10.1111/j.1365-2648.1994.tb01164.x
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting job satisfaction of nurses who work in long‐term care

Abstract: A questionnaire developed by the authors was sent to 1000 nurses in various specialty areas. It was used to assess degree of job satisfaction, reasons for dissatisfaction, and the relationships of the work setting and sociodemographic data. Because the authors wanted to compare nurses who work primarily with older adults within and outside long-term care, the percentage of time spent caring for patients aged over 60 was also studied. The degree of job satisfaction between nurses working in long-term care was c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0
2

Year Published

1997
1997
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(34 citation statements)
references
References 6 publications
0
32
0
2
Order By: Relevance
“…Within the health workforce, studies have documented that nurses (Carr & Kazanowski, 1994;Farrell 1999;Quine 2001) and junior doctors (Quine 2002) experience high levels of bullying. A study of a community health trust in the UK in 1996 found that 38% of employees had experienced one or more types of bullying within the previous year (Quine 1999).…”
Section: How Common Is Workplace Bullying?mentioning
confidence: 99%
“…Within the health workforce, studies have documented that nurses (Carr & Kazanowski, 1994;Farrell 1999;Quine 2001) and junior doctors (Quine 2002) experience high levels of bullying. A study of a community health trust in the UK in 1996 found that 38% of employees had experienced one or more types of bullying within the previous year (Quine 1999).…”
Section: How Common Is Workplace Bullying?mentioning
confidence: 99%
“…These consequences can come in the form of loss of productivity at work, 10 time off work due to injuries, 11,12 higher perceived physical job demands and workload. 13 These aspects, in combination with environmental and organizational factors, directly affect job satisfaction, 14 which ultimately affects staff retention and recruitment. 15 The triad of high injury rates, existing shortages in the work force and increases in the aged population raises concerns over our ability to satisfy the growing demand for eldercare.…”
Section: Introductionmentioning
confidence: 99%
“…However, RNs do express a sense of professional pride and satisfaction in their ability to provide safe, competent care for older people and to be creative and flexible in care planning and delivery. Carr and Kazanowski identify networking with others in long‐term care as essential for increasing such awareness and creativity in order to achieve quality care outcomes 13 . However, participants in this study report that such opportunities are limited, and this has an impact upon levels of satisfaction and sense of value.…”
Section: Discussionmentioning
confidence: 85%
“…These images are conveyed through the media and nursing profession and are supported by organizational and government failure to recognize value through adequate remuneration and staffing levels. This tension between nursing values and those mediated by political and social forces further influences job satisfaction and, ultimately, the retention of qualified nursing staff in aged care 13,20 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation